Differential distribution of macroinvertebrate associated with water quality. Issue 1 (24th January 2023) - Thakur, Yojana; Grover, Aseem; Sinha, Reshma
Abstract: Streams and rivers are the major source of drinking water and irrigation in many developing countries. Stream health is a major criterion and regulator of the health of its dependents (invertebrates, aquatic flora, fishes, animals, and humans). For the sustenance of a balanced ecosystem, a mutual existence between flora and fauna along with other abiotic factors is a prerequisite. Benthic fauna lying on the riverbed serves as a food source for fish, larger insects, birds, etc. Nowadays, most freshwater bodies are getting polluted through various anthropogenic activities like mining, land‐use practices (fertilizers and insecticides), industrial effluent, and sewage inlet. Due to the water contamination, there have been observed changes in the physicochemical parameters of the water. The macroinvertebrate species being sensitive to these changes play an important role not only in determining the health of the water body but also in regulating the ecosystem. After review, it was observed that order like Diptera dominated in various locations, comprising of family Ceratopogonidae and Chironomidae, followed by order Trichoptera and Coleoptera. Species belonging to family Baetidae and Chironomidae possess pollution tolerance capabilities; additionally, these species can survive at a wide range of temperatures. Species from families such as Simuliidae showed their existence at varying water velocities. Families like Limnephilidae, Simuliidae, and Glossosomatidae exhibited their survival in fast moving water whereas Notonectidae, Hydrophilidae Gomphidae, Coenagrionidae, Libellulidae, Aeshnidae, and Dryopidae indicated species of low waterflow. Species of the family Tipulidae have been related to areas of high conductivity, whereas Gomphidae, Dryopidae, and Glossomatidae as species of low conductivity. Hydrophilidae and Notonectidae dominated high temperature areas. The present study will put forth before the government, current scenario of macroinvertebrate structure depending on the different characteristics of the water. This will help in regulating and controlling water pollution. Abstract: 摘要 溪流与河流是许多发展中国家饮用水和灌溉的主要来源。溪流健康是其依附者 (无脊椎动物、水生植物、鱼类、动物和人类)健康的主要标准和调节器。为了维持平衡的生态系统, 动植物之间的相互依存和其他非生物因素是必要的。河床上的底栖动物群是鱼类、大型昆虫、鸟类等的食物来源。如今, 大多数淡水水体都受到各种人类活动的污染, 如采矿、土地利用 (施放化肥和杀虫剂)、工业废水、 以及污水入口。由于水污染, 已经观察到水的物理化学参数发生变化。对这些变化敏感的大型无脊椎动物物种在决定水体健康和调节生态系统方面发挥着重要作用。调查发现, 双翅目在不同地点占主导地位, 包括蠓科和摇蚊科, 其次是毛翅目和鞘翅目。四节蜉科和摇蚊科物种具有耐污染能力, 此外还可以在很广的温度范围内生存。在不同的水流速度下发现了蚋科类物种。沼石蛾科、蚋科和舌石蛾科等科在快速流动的水中表现出生存能力, 而仰泳蝽科、水龟虫科、春蜓科、细蟌科、蜻蜓科、晏蜓科和泥虫科则表明它们是低水流物种。大蚊科的物种与高电导率区域有关, 而春蜓科、泥虫科和舌石蛾科与低电导率区域有关。水龟虫科和仰泳蝽科在高温区占主导地位。本研究将向政府提出"根据水的不同特征发现大型无脊椎动物结构的当前情景"。这将有助于调节和控制水污染。 Abstract: Los arroyos y ríos son la principal fuente de agua potable y riego en muchos países en desarrollo. La salud de los arroyos es un criterio importante y un regulador de la salud de sus dependientes (invertebrados, flora acuática, peces, animales y humanos). Para el sustento de un ecosistema equilibrado, la existencia mutua entre la flora y la fauna junto con otros factores abióticos es un requisito previo. La fauna bentónica que se encuentra en el lecho del río sirve como fuente de alimento para peces, insectos más grandes, pájaros, etc. y entrada de aguas residuales. Debido a la contaminación del agua, se han observado cambios en los parámetros fisicoquímicos del agua. Las especies de macroinvertebrados que son sensibles a estos cambios juegan un papel importante no solo en la determinación de la salud del cuerpo de agua sino también en la regulación del ecosistema. Después de la revisión, se observó que el orden Diptera dominaba en varios lugares, que comprende la familia Ceratopogonidae y Chironomidae, seguido por el orden Trichoptera y Coleoptera. Las especies pertenecientes a la familia Baetidae y Chironomidae poseen capacidades de tolerancia a la contaminación, además pueden sobrevivir en un amplio rango de temperaturas. Mientras que especies de familias como Simuliidae mostraron su existencia a diferentes velocidades del agua. Familias como Limnephilidae, Simuliidae y Glossosomatidae exhibieron su supervivencia en aguas de rápido movimiento mientras que Notonectidae, Hydrophilidae Gomphidae, Coenagrionidae, Libellulidae, Aeshnidae y Dryopidae indicaron especies de bajo flujo de agua. Las especies de la familia Tipulidae se han relacionado con áreas de alta conductividad, mientras que Gomphidae, Dryopidae y Glossomatidae como especies de baja conductividad. Hydrophilidae y Notonectidae dominaron las áreas de alta temperatura. El presente estudio expondrá ante el gobierno el escenario actual de la estructura de los macroinvertebrados en función de las diferentes características del agua. Esto ayudará en la regulación y control de la contaminación del agua.